2018
DOI: 10.1002/ece3.4123
|View full text |Cite
|
Sign up to set email alerts
|

The indestructible insect: Velvet ants from across the United States avoid predation by representatives from all major tetrapod clades

Abstract: Velvet ants are a group of parasitic wasps that are well known for a suite of defensive adaptations including bright coloration and a formidable sting. While these adaptations are presumed to function in antipredator defense, observations between potential predators and this group are lacking. We conducted a series of experiments to determine the risk of velvet ants to a host of potential predators including amphibians, reptiles, birds, and small mammals. Velvet ants from across the United States were tested w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
0
17
0
3
Order By: Relevance
“…First, as is mentioned above, the length and agility of the sting, combined with their extraordinarily hard cuticle, aposematic coloration, and stridulation enables velvet ants to quickly and effectively train predators to avoid them. Gall et al (in press) , for example, found that when a lizard (in this study the lizard was Aspidoscelis tigris ) attacks a velvet ant, it is unable to crush it because of the hard cuticle, as the lizard attempts to manipulate the velvet ant in its mouth, the velvet ant is quickly able to sting the lizard. Once released, the aposematic coloration of the velvet ant apparently facilitates rapid learning in the lizard.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…First, as is mentioned above, the length and agility of the sting, combined with their extraordinarily hard cuticle, aposematic coloration, and stridulation enables velvet ants to quickly and effectively train predators to avoid them. Gall et al (in press) , for example, found that when a lizard (in this study the lizard was Aspidoscelis tigris ) attacks a velvet ant, it is unable to crush it because of the hard cuticle, as the lizard attempts to manipulate the velvet ant in its mouth, the velvet ant is quickly able to sting the lizard. Once released, the aposematic coloration of the velvet ant apparently facilitates rapid learning in the lizard.…”
Section: Discussionmentioning
confidence: 57%
“…Velvet ants, on the other hand, parasitize hosts (immature hymenoptera) that are already immobile, and it has been suggested that their sting and associated venom is primarily used for defense ( Schmidt, 2016 ). Highly toxic venom for defense might be selected against, as it would be more beneficial for a velvet ant to inflict pain, but not mortally wound a potential predator facilitating learned avoidance, which has been demonstrated in feeding trials with various vertebrates ( Gall et al, in press ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a more comprehensive study would include multiple predator types. In the few such studies to date, no universal antipredator defenses have been found (Honma et al 2006;Gall et al 2018). Furthermore, antipredator defenses can vary intraspecifically.…”
Section: Multiple Predator Species and Sufficient Replicationmentioning
confidence: 99%
“…Surprisingly, given their presumed importance, defensive venoms have been poorly studied [20,22,38]. Only a handful of investigations have demonstrated the efficacy of such venoms against natural predators [21,[38][39][40][41][42][43]. Moreover, no study has attempted to tease apart the relative contributions of the painful vs. toxic elements to a venom's effectiveness in deterring an enemy, perhaps because most defensive cocktails contain both components [23].…”
Section: Introductionmentioning
confidence: 99%